Doses and methods of potassium application on soybean in a cerrados soil of Bahia, Brazil - de Oliveira, Francisco Assis; e Silva, José Joaquim Santana; Vilela, Lourival; de Sousa, Djalma martinhão Gomes (Pesquisa Agropecuaria Brasileira, 1992)
For three years, an experiment was carried out in an oxisoil (Red-Yellow Latosol, sandy loam soil) in the State of Bahia, Brazil, to study the effects of different levels of potassium fertilizer (0, 90, 120, 180, 270, and 280 kg/ha de K2O on two different application methods), and their effect on soybean yield. The experimental design utilized was a randomized block with thirteen treatments and four repetitions. There was an increase on soybean yield in the first year due to the application of 60 kg/ha of K2O from both the broadcast and hand placement treatments. However in the second and third years, the rate of 180 kg/ha of K2O promoted the maximum return from K fertilizer. Rates smaller than 180 kg/ha of K2O did not show any residual effect on soybean yield. The maximum yields were associated to the K levels in the leaves equal or above 1.31%. Rate of 120 kg/ha of K2O or more increased the K loss by leaching to a layer down to 30 cm by the first year.